Ética en el periodismo digital en tiempo real: un estudio de caso en diario La Hora Loja y Hora 32, periodo 2023-2024. - Calva Ortiz, Cinthia Yamileth (2024)
Digital journalism presents a new face of communication: it gives rise to a more interactive, connected and participatory journalism, facilitating the dissemination of information by means of social networks through intelligent technological devices. This new model brings with it certain characteristics and disadvantages for journalistic ethics because it compromises important values of the profession. The research focuses on the newspapers La Hora Loja and the digital native media Hora 32, in order to identify the ethical principles and professional standards that guide the work of its journalists in the creation and dissemination of live content. The methodology used is mixed, by means of interviews, an observation matrix, and a survey. Thus, 415 Facebook Live publications from both media are analyzed through a matrix that divides ethical principles and subcategorizes the practices aligned to them. In addition, the survey is applied to 383 people to know their perception of the live content. At the same time, to identify the way in which ethics is developed within the newspapers, two members of each newspaper are interviewed, and as part of the panel of experts, three journalists from outside the analyzed media, who have more than ten years of experience in the field of journalism, are considered. The results reflect the ethical commitment of the media and underline the need to continue training the team of journalists to maintain and increase the ethical standards of a responsible professional work. Keywords: digital journalism, ethical practices, digital environments, real-time content, broadcasts.